2014
DOI: 10.1186/1479-5876-12-134
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of FOXM1 predicts poor prognosis and promotes cancer cell proliferation, migration and invasion in epithelial ovarian cancer

Abstract: BackgroundThe Forkhead box M1 (FOXM1), an important regulator of cell differentiation and proliferation, is overexpressed in a number of aggressive human carcinomas. The purpose of this study was to examine the expression levels of FOXM1 in epithelial ovarian cancer (EOC), to identify the relationship between FOXM1 expression and patient survival, and to investigate the role of FOXM1 in human ovarian cancer development.MethodsImmunohistochemical analysis for FOXM1 was performed in a total of 158 ovarian tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 28 publications
4
65
0
Order By: Relevance
“…Previously, FOXM1 has been reported to promote the expression of many factors that are involved in the degradation of extra cellular matrix and angiogenesis such as uPAR, MMP-2, MMP-9, and vascular endothelial growth factor A (VEGF-A) [16,17]. Thus, qRT-PCR and Western blotting assays were performed to detect the effects of miR-149 or FOXM1 expression on the mRNA and protein expression of MMP-2, MMP-9, VEGF-A and uPAR in CRC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, FOXM1 has been reported to promote the expression of many factors that are involved in the degradation of extra cellular matrix and angiogenesis such as uPAR, MMP-2, MMP-9, and vascular endothelial growth factor A (VEGF-A) [16,17]. Thus, qRT-PCR and Western blotting assays were performed to detect the effects of miR-149 or FOXM1 expression on the mRNA and protein expression of MMP-2, MMP-9, VEGF-A and uPAR in CRC cells.…”
Section: Resultsmentioning
confidence: 99%
“…MMP-2 and MMP-9 principally function in tumor invasion and migration (49), whereas VEGF is a key factor in angiogenesis (50,51). In epithelial ovarian cancer cells, FOXM1 downregulation led to reduced expression of MMP-2, MMP-9 and VEGF (52). In a previous study, the present authors used RNAi to inhibit the expression of FOXM1 in cervical cancer cells, which consequently suppressed the activity and expression of MMP-2, MMP-9 and VEGF (18).…”
Section: A B C D E F G Hmentioning
confidence: 86%
“…Interestingly, the effect exerted by miR-194 on FoxM1 was suggested to be involved in the EMT process of neoplasms [21], and several microarray assays revealed that FoxM1 was highly expressed within > 20 solid neoplasms, including hepatocellular carcinoma, pancreatic adenocarcinoma, mastocarcinoma, ovarian cancer, lung cancer and CRC [43][44][45][46][47]. Besides, FoxM1 was over-expressed within actively-proliferating tumor cells, and it functioned to facilitate cell multiplication mainly by regulating cell cycle-specific genes [48].…”
Section: Discussionmentioning
confidence: 99%